Mesenchymal stem cells shuttling miR-503 via extracellular vesicles enhance glioma immune escape. (1st January 2022) - Wang, Xiao-Song; Yu, Xiao-Jun; Wei, Kang; Wang, Shan-Xi; Liu, Qi-Kun; Wang, Ying-Guang; Li, Han; Huang, Cheng
ABSTRACT: Glioma is emerging as an aggressive type of glioma characterized by invasive growth pattern and dismal oncologic outcomes. microRNAs (miRNAs) have been attracting research attention in tumorigenesis. Herein, the aim of the current investigation was to explore the functional role of mesenchymal stem cells (MSCs)-derived extracellular vesicles (EVs) containing miR-503 in glioma. The glioma tissues and corresponding normal brain tissues were collected from patients with glioma, followed by quantification of miR-503, kinesin family member 5A (KIF5A) and interleukin-7 (IL-7). EVs were isolated from bone marrow MSCs and identified by transmission electron microscope and nanoparticle tracking analysis. EVs from miR-503 mimic-transfected MSCs, miR-503 agomir, , oe-KIF5A, or sh-IL-7 was delivered into glioma cells to determine their effects on biological behaviors of glioma and T cells as well as the release of immunosuppressive factors. Lastly, a mouse model of glioma was developed to validate the function in vivo . miR-503 was expressed at a high level in glioma tissues while KIF5A was poorly expressed and targeted by miR-503. Furthermore, miR-503 loaded in MSC-EVs or upregulated miR-503 was demonstrated to facilitate glioma cell proliferation, migration and invasion accompanied by promoted release of immunosuppressive factors. Effects of overexpressed KIF5A on T cell behavior modulation were dependent on the IL-7 signaling pathway. Such results were reproduced in mice with glioma. Collectively, the discovery of miR-503 incorporated in MSC-EVs being a regulator that controls immune escape in glioma provides a novel molecular insight that holds promises to develop therapeutic strategies against glioma.